Analysis of Training Program in Front Office Department at Aryaduta Bali Hotel - Luh Putu Diah Ayu Savitri; I Gusti Agung Gede Witarsana; Desak Gede Chandra Widayanthi; I Wayan Restu Darmawan (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
Training program evaluation is highly necessary and important to improve the business, particularly in the hospitality business. The aim of this research is to analyze the quality of training programs held for employees in the Front Office Department at Aryaduta Bali Hotel based on the Kirkpatrick Model and finding out a possible suggestion for improvement that could be done to enhance the quality of training programs. The data for this study was obtained by distributing an online questionnaire and conducting interviews. To validate the data, testing was done through data triangulation. As a result of this study, there are 2 criteria that show that the training program needs improvements more on how to satisfy the participants and how to more effectively evaluate the program. To improve these aspects, anonymous evaluation to gather detailed and objective input from the participant is suggested to be done.